The Potential of Heavy Metal Plumbum (Pb) Degradation Agents in Composted Raw Materials from Inked Paper Waste - Hesti Kurniahu; Annisa Rahmawati; Sriwulan Sriwulan; Riska Andriani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
The pre-composting process of inked waste paper serves to reduce Pb levels in compost raw materials in the form of inked waste paper by using Pb (lead) degradation agents in the form of corn cob charcoal, activated charcoal, PGPR and cow rumen liquor. This study intends to ensure the quality of waste compost materials in the form of inked waste paper after being given pb degradation agents. Pb test using AAS (Atomic Absorbtion Spectrophotometer) method and cellulolytic bacteria test using pour plate method. The data were statistically tested with Anova and LSD advanced tests. From the results of observations, it was known that the provision of Pb degradations agents in the form of activated charcoal and PGPR has a significant effect on Pb levels and has met SNI 19-7030-2004. Meanwhile, the highest number of cellulolytic bacteria was found in the treatment of giving cow rumen liquor followed by PGPR treatment